Health Behavior, Status, and Outcomes Among a Community-Based Sample of Lesbian and Bisexual Women - Bostwick, Wendy B. (LGBT Health, 2015)
Purpose: To compare health behaviors, and physical and mental health outcomes in a community-based sample of bisexual and lesbian women. Methods: The Chicago Health and Life Experiences of Women (CHLEW) study is a longitudinal study of sexual minority women's health. Wave 3 of the CHLEW used a modified version of respondent-driven sampling to recruit a supplemental sample of bisexual-identified women into the study, with an additional focus on younger women, and Black and Latina women. Face-to-face interviews were conducted and data were captured using computer-assisted interviews. Data from the supplemental Wave 3 sample are reported here. Results: Bisexual (n=139) and lesbian women (n=227) did not differ on most health outcomes, either in terms of prevalence or adjusted odds. Bisexual women were at higher risk of ever being diagnosed with a sexually transmitted infection (STI) (AOR=3.01) and scoring 10 or more on the Center for Epidemiologic Studies Depression Scale (CES-D) (AOR=1.73) compared to lesbian women. Conclusion: In contrast to the prevailing view of bisexual women as being at higher risk for many/most negative health outcomes, we found relatively few differences between bisexual and lesbian women in the current study. Additional research is needed to better understand risk and resilience factors among bisexual women specifically, and sexual minority women more broadly.